STORCH Brazil: multicenter cohort study protocol to investigate neurodevelopmental paths and functioning in infants exposed to STORCH in Brazil - Daniele Almeida Soares-Marangoni; Amanda de Oliveira Arguelho; Ayrles Silva Gonçalves Barbosa Mendonça; Carine Carolina Wiesiolek; Carolina Daniel de Lima-Alvarez; Eloá Maria dos Chiquetti; Everton Falcão de Oliveira; Márcio José de Medeiros; Silvana Alves Pereira; Renata Hydee Hasue (BMC Pediatrics)
Abstract Background The acronym STORCH encompasses gestational infections that can lead to congenital syndromes or adverse neurological outcomes in children. In Brazil and worldwide, there has been an alarming increase in confirmed cases of STORCH in recent years. However, no study has examined the impact of STORCH on infants’ neurodevelopmental outcomes in a large, multi-center cohort, recruiting a substantial number of participants, with analysis across a broad set of variables and ages and based on the International Classification of Functioning, Disability and Health (ICF) model. Objective To examine the association between the exposure to classic STORCH (syphilis, toxoplasmosis, rubella, cytomegalovirus infection, and herpes simplex) on components of functioning in infants from 3 to 24 months old in Brazil. Methods We propose a multi-center prospective cohort study that includes data collection in at least one city from each geographical region of Brazil. A proposed total sample size of 296 infants will be included at 3 months (12–15 weeks post term). They will be equitably divided into: (a) an exposed group (n = 148), consisting of those diagnosed with any congenital STORCH infection or whose mothers experienced prenatal STORCH infection; (b) an unexposed group (n = 148). Assessments are carried out longitudinally at 3, 6, 9, 12, 18, and 24 months of age. Assessment tools include Prechtl’s General Movements Assessment, Hammersmith Infant Neurological Examination, Alberta Infant Motor Scale; Bayley Scales of Infant and Toddler Development; Survey of Well-being of Young Children; Autism Observational Scale for Infants; Modified Checklist for Autism in Toddlers; Child Behavior Checklist; and Young Children’s Participation and Environment Measure. Descriptive analyses, including the calculation of relative risk, and logistic regressions will be conducted to examine the association between gestational exposure to STORCH agents and infants’ responses/outcomes. Discussion The STORCH Brazil study will investigate the impact of STORCH exposure on functioning, including neurodevelopmental trajectories, in infants during their first two years, aligning with the ICF framework. This will enhance understanding of the characteristics and needs of STORCH-exposed infants, aiding therapists in making informed clinical decisions. The results might support public policies tailored to this population. Findings will be disseminated to ensure knowledge translation. Clinical trial number Not applicable.